2013
DOI: 10.3109/08039488.2013.846410
|View full text |Cite
|
Sign up to set email alerts
|

Children and adolescents in the Psychiatric Emergency Department: A 10-year survey in Copenhagen County

Abstract: The number of presenting psychiatric emergencies has increased over the last 10 years. Comparing symptoms from 2003 and 2006 showed a significant rise in their severity. This study highlights the need for 24-h access for acute evaluation by physicians skilled in child and adolescent psychiatry, and raises concern that the severity could increase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 8 publications
1
22
0
4
Order By: Relevance
“…While the overall prevalence of mental health conditions in youth has remained relatively stable [1], many recent studies have reported an increase in psychiatric emergencies in children and adolescents. Such increase has been noted in the United States [2][3][4][5], Canada [6][7][8], and Europe [9][10][11]. Over the same period, most countries have reduced the number of child and adolescent psychiatric inpatient beds [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…While the overall prevalence of mental health conditions in youth has remained relatively stable [1], many recent studies have reported an increase in psychiatric emergencies in children and adolescents. Such increase has been noted in the United States [2][3][4][5], Canada [6][7][8], and Europe [9][10][11]. Over the same period, most countries have reduced the number of child and adolescent psychiatric inpatient beds [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Many (39%) children and youth presenting to EDs for mental health concerns have several repeat visits, returning to the ED three or more times, compared to 15% returning to the ED for other conditions [2]. Furthermore, this is not unique to Canada, with similar findings reported in the US [3], and Norway [4].…”
Section: Introductionmentioning
confidence: 87%
“…3 Department of Psychiatry, IWK Health Centre, Halifax, Nova Scotia, Canada. 4 Dalhousie University Department of Psychiatry, Halifax, Nova Scotia, Canada. 5 Dalhousie University School of Occupational Therapy, Halifax, Nova Scotia, Canada.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…6,[14][15][16][22][23][24] Esto se observó en la investigación realizada, en la que muchos de los niños-adolescentes procedían de otras localidades de la provincia de Córdoba.…”
Section: 18unclassified